Current advances of plant-based vaccines for neurodegenerative diseases - Bravo-Vázquez, Luis Alberto; Mora-Hernández, Erick Octavio; Rodríguez, Alma L.; Sahare, Padmavati; Bandyopadhyay, Anindya; Duttaroy, Asim K.; Paul, Sujay (MDPI, 2023)
Neurodegenerative diseases (NDDs) are characterized by the progressive degeneration and/or loss of neurons belonging to the central nervous system, and represent one of the major global health issues. Therefore, a number of immunotherapeutic approaches targeting the non-functional or toxic proteins that induce neurodegeneration in NDDs have been designed in the last decades. In this context, due to unprecedented advances in genetic engineering techniques and molecular farming technology, pioneering plant-based immunogenic antigen expression systems have been developed aiming to offer reliable alternatives to deal with important NDDs, including Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis. Diverse reports have evidenced that plant-made vaccines trigger significant immune responses in model animals, supported by the production of antibodies against the aberrant proteins expressed in the aforementioned NDDs. Moreover, these immunogenic tools have various advantages that make them a viable alternative for preventing and treating NDDs, such as high scalability, no risk of contamination with human pathogens, cold chain free production, and lower production costs. Hence, this article presents an overview of the current progress on plant-manufactured vaccines for NDDs and discusses its future prospects.